Effect of an application with video visual scene displays on communication during play: pilot study of a child with autism spectrum disorder and a peer. (2nd October 2019) - Laubscher, Emily; Light, Janice; McNaughton, David
Abstract: Children with autism spectrum disorder (ASD) and limited speech are at risk for exclusion from pretend play with their peers due in part to communication difficulties. The purpose of this pilot study was to examine the effect of an intervention package, consisting of tablet-based augmentative and alternative communication technology with video visual scene displays (video VSDs) and instruction, on communication between a child with ASD and a peer with typical development across three play activities. One dyad, consisting of the child with ASD and the peer, participated in this study. A multiple probe design across three play activities was used to evaluate the effect of the intervention on the number of symbolic communicative turns taken by the participant with ASD. At baseline, this participant demonstrated minimal symbolic communication related to play activities. Following the intervention, he demonstrated an increase in symbolic communicative turns across all three play activities, with a large overall effect size. The results of this study provide preliminary support for use of a video VSD intervention to support communication for children with ASD and limited speech during pretend play with their peers.